Left bundle branch pacing and cardiac remodeling in HF patients with type 2 diabetes mellitus: epigenetic pathways and clinical outcomes - Sardu, Celestino; Vittoria Marfella, Ludovica; Giordano, Valerio; Lepre, Caterina Claudia; D’Amico, Giovanbattista; Volpicelli, Mario; Contaldi, Carla; Galiero, Raffaele; Caturano, Alfredo; Casolaro, Flavia; Sasso, Ferdinando Carlo; Uran, Carlo; et al. (Frontiers in Pharmacology, 2024)
Background: Left bundle branch (LBB) pacing could achieve cardiac resynchronization therapy (CRT) in patients that cannot be resynchronized via the placement of the left ventricle (LV) led into the coronary sinus. LBB-pacing could determine amelioration of cardiovascular outcomes in heart failure (HF) patients with LBB and affected by type 2 diabetes mellitus (T2DM).Study hypothesis: LBB pacing could increase CRT responders and lead to the best clinical outcomes in HF patients with T2DM, inducing cardiac remodeling and improving left ventricle ejection fraction (LVEF) via microRNAs (miRs) modulation.In an observational multicenter study, we enrolled 334 HF patients with LBB block and indication to receive LBB-pacing to achieve CRT. In these patients, we evaluated, at 1 year of follow-up, CRT responders' rate, clinical outcomes, and miRs expression.Results: At 1 year of follow-up, we had 223 responders (66.8%), 132 hospitalizations for HF (39.5%), 24 cardiac deaths (7.2%), and 37 all-cause deaths (11.1%), with higher rate of HF hospitalizations (77 (69.4%) vs. 55 (24.7%), p<0.05), and cardiac deaths (13 (11.7% vs. 11 (4.9%), p<0.05) in Non-responders vs. Responders. At follow-up end, we found a lowest expression of miR-26, miR-29, miR-30, miR-92 and miR-145 in Non-responders vs. Responders to LBB-pacing (p<0.05), and a direct correlation between miR-30 (0.340, [0.833-1.915]; p0.001), 6 minuteswalking-test (6MWT; 0.168, [0.008-0.060]; p 0.011), angiotensin-receptor-neprilysin-inhibitors (ARNI; 0.157, [0.183-4.877]; p 0.035) and sodium-glucose-trasporter-2-inhibitors (0.245, [2.242-7.283]; p 0.001) and LVEF improvements. CRP inversely correlated with LVEF improvement (-0.220, [-(0.066-0.263)]; p 0.001). ARNI (1.373, CI 95% [1.007-1.872], p 0.045), miR-30 (2.713, CI 95% [1.543-4.769], p 0.001), and 6MWT (1.288, CI 95% [1.084-1.998], p 0.001), were predictors of LBB-pacing Responders at 1 year of follow-up.Conclusions: LBB-pacing responders evidenced miRs modulation, which was linked to significant amelioration of cardiac pump. Specifically, miR-30 linked to amelioration of the cardiac pump and predicted responders' event at 1 year of follow-up in T2DM patients.